Najstarejši ohranjeni knjižnični katalog na Slovenskem - Južnič, Stanislav (Knjižnica, 2008)
The article presents a professional work of the librarian Filip Terpin from Selca (North of Škofja Loka, Slovenia). Terpin's catalogue of the bishop's library in Gornji Grad is the oldest catalogue in Slovenia, with the exception of some protestant book lists which date even earlier. It was created in 1655, thirteen years before the second oldest preserved catalogue, which was made by his contemporary Schönleben. Terpin's catalogue is carefully described and compared with the Schönleben's list of Volf Engelbert Auersperg's library, which was made in 1668. The author highlights the professional relations between the two librarians and describes the destiny of the Primož Trubar's and the bishof's libraries in Gornji grad. The article is a part of an extensive research set out to identify and explore the provenience of science books which were under the Terpin's custody in the Gornji grad library, especially of those owned by the Slovenian protestants or even Primož Trubar himself.
Keywords: Terpin, Filip, 1605-1683; Schönleben, Janez Ludvik, 1618-1681; zasebne knjižnice; knjižnični katalogi; biografije; Slovenia; Slovenija; zgodovinski pregledi